Knowledge of E-Learning is a Must in 21st Century Digital Education Era - Soe Thane (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
E-learning is now used on a global scale. It works together. One can learn whenever they want, as often as they want, and on their own schedule with e-learning. Other time-saving features include not having to commute to and from the classroom, being able to select only the portions of the course that interest them, and having uninterrupted time. Because of the rapid developments in technology and learning systems, the majority now accepts it. This revolution was sparked by the invention of computers, and as time goes on and we become dependent on smartphones, tablets, etc., these gadgets now play a significant role in classroom instruction. Over time, electronic educational resources like optical discs and flash drives are replacing books. It is possible to share knowledge using the Internet, which is accessible 24/7 from anywhere. This is how online learning develops. Online learning, often known as e-learning, may be traced back to the 1990s, when the trend first began to take off. The development of personal computers accelerated during this decade. Online skill learning was made simpler and more accessible through e-learning. E-learning can take many different forms, including online training programs, blended learning, mobile learning, podcasts, video training, microlearning, and webinars. E-learning platforms are being introduced one after another. Coursera, Skillshare, Udemy, Codecademy, Edx, Pluralsight, Future Learn, and Moodle are a few of the top online learning tools. We also have online course platforms like LearnWorlds, Teachable, Thinkific, Kajabi, and Podia in addition to online learning platforms.